High serum angiopoietin-like protein-4 levels are associated with gestational hypertension and preeclampsia: a case-control study - Acikgozoglu, M. Kagan; Pala, Sehmus; Atilgan, Remzi; Ilhan, Nevin; Ilhan, Necip (Walter de Gruyter Gmbh, 2024)
Objectives Investigation of angiopoietin-like protein-4 (ANGPTL-4) and vascular endothelial growth factor A (VEGF-A) levels as a biochemical marker in gestational hypertension (GH) and preeclampsia (PE), which are known to have important roles in the maintenance of angiogenesis and endothelial functions. Methods Total of 90 patients included in this case-control study. Group 1 (G1) (n=30)=patients with healthy pregnancy between 37 and 41 weeks, G2 (n=30)=patients diagnosed with gestational hypertension between 20 and 37 weeks, G3 (n=30)=patients diagnosed with preeclampsia between 20 and 37 weeks. The sera obtained from the patients were stored at -80 degrees C until they were studied. Demographic parameters, systolic, diastolic and mean arterial blood pressure were recorded. VEGF-A and ANGPTL-4 levels were studied with enzyme-linked immunosorbent assay (ELISA) kit. Results The mean age was similar in both groups. The number of primigravida pregnant was higher in G2 and G3 than in G1. Gestational week was more advanced in G1 compared to G2 and G3. While ANGPTL-4 and VEGF-A levels were similar between G2 and G3, they were significantly higher in both groups compared to G1. Conclusions We showed that ANGPTL-4 and VEGF-A levels were elevated in maternal serum in GH and PE cases. Increased maternal serum ANGPTL-4 levels may be a biomarker that can be used in the early diagnosis of PE.
Keywords: pregnancy; preeclampsia; gestational hypertension; ANGPTL-4; VEGF-A